(untitled) (Nepal Medical College Journal, 2021)
This study was carried out to see the safety and efficacy of mifepristine as pre-induction cervical ripening agent along with misoprostol in induction of labour. It was a study done from January to June 2020 in Department of Obstetrics and Gynecology, Nepal Medical College Teaching Hospital. Total 120 patients were included in this study. Out of which, 60 women were be kept in test group who were induced by mifepristone and misoprostol and 60 women were kept in control group induced by misoprostol only. Patient characteristics, improvement of bishop score, maternal and neonatal outcome was recorded. Chi- square and T- Test were used to compare the result. Patient characteristics and the Bishop score at zero-hour of both the groups were similar. The mean bishop score 48 hours after use of mifepristine in test group was significantly increased in test group vs control group (P<0.0001). There were total 12(20%) patient who went in to labour with mifepristone only without the use of misoprostol. Total number of normal delivery was more (p value=0.003) and cesarean was less (p=0.013) in test group than in control group. The instrumental delivery in both test and control group were same. The adverse effect and neonatal outcome was similar in both the regime. Thus mifepristone as pre-induction cervical ripening agent is a safe and efficient drug